Educação CTS e competências socioemocionais: um estudo de caso em escola pública no interior paulista - Pereira, Victor Marques (2024)
The teaching of socio-emotional skills has become increasingly relevant, both in order to enable healthier relationships and as a tool to prevent violence, both inside and outside the school environment. The literature shows that school violence stems partly from social conflicts which arise due to disrespect and discrimination, in which socio-emotional competence can therefore be a key element in tackling. However, some teaching-learning and school management gaps still exist for this teaching to become effective. Considering this scenario, the general objective of this research was to reflect on the contributions of STS education to the teaching and learning of socio-emotional skills by teachers. The specific objectives were: to identify elements of the environment and relationships between teachers and members of the school community that influence the teaching-learning process and to analyze the teachers' pedagogical repertoire for teaching socio-emotional competences, from the perspective of STS Education. For this research, a case study was carried out in a state primary school in a municipality within the state of São Paulo. Data was collected through interviews with the participants: teachers and members of the pedagogical coordination team. Using a qualitative research approach, the data collected was interpreted using the thematic analysis technique. The results indicated that the teachers did not have institutional support for the complementary pedagogical training needed to work with socio-emotional education, but they did have a certain repertoire related to the subject. The school had adequate infrastructure for the teaching-learning process and a good relationship between management and teachers, but faced challenges in teacher-parents and teacher-teacher relationships. In conclusion, STS education can contribute to the teaching of socio-emotional skills through democratic education and the establishment of dialogical relationships between students and teachers, can support the development of social skills, assertiveness and citizenship, as well as promoting a tripartite dialog between the STS field, education and psychology, fostering future interdisciplinary research in the area.